1996
DOI: 10.1016/s1057-0810(96)90024-4
|View full text |Cite
|
Sign up to set email alerts
|

Professional Stock Analysts’ Recommendations

Abstract: Conclusions regarding analyst performance often depend on the evaluation technique employed. Using a wide variety of techniques, wefind that although there is some evi- dence that analysts do have the ability to identify undervalued and overvalued securities, individual investors generally experience inferior portfolio performance by following analyst recommendations published in the ‘Market Highlights” section of USA Today (even before transaction costs are included). Asaresult,individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…Research on the role of recommendations in the investment process and their effectiveness in valuing listed companies is ambiguous. The first study of the impact of recommendations on price changes revealed that most of the recommendations did not constitute a significant source of information to the advantage of its holder (Cowles, 1933), as was also confirmed by Walker and Hatfield (1996). Stickel (1995) noted that the impact of stock market recommendations on investment decisions of investors varies, which is conditioned by the fact that investors, following the reputation of a brokerage house, do not treat all recommendations in the same way.…”
Section: Importance Of Stock Market Recommendationsmentioning
confidence: 99%
“…Research on the role of recommendations in the investment process and their effectiveness in valuing listed companies is ambiguous. The first study of the impact of recommendations on price changes revealed that most of the recommendations did not constitute a significant source of information to the advantage of its holder (Cowles, 1933), as was also confirmed by Walker and Hatfield (1996). Stickel (1995) noted that the impact of stock market recommendations on investment decisions of investors varies, which is conditioned by the fact that investors, following the reputation of a brokerage house, do not treat all recommendations in the same way.…”
Section: Importance Of Stock Market Recommendationsmentioning
confidence: 99%
“…In his research he received a variety of results for different institutions -that means that investors do not treat all recommendations in the same way. However, the analyses made by Walker and Hatfield [1996] showed that investors do not have additional benefits coming from the use of recommendations. In a study made by Clark et al the recommendations issued in 1995-2001 were tested.…”
Section: Previous Studiesmentioning
confidence: 99%
“…The most widely accessed sites both by brokerage firms as well as investors, were selected. Similar studies, used newspaper information like "USA Today" and "Wall Street Journal" in Barber and Loefler (1993), Lieu, Smith and Syed (1993), Holloway (1981 and1983), Walker and Hatfield (1996) etc. Recent works derived information from "Zacks Investment Research", which includes a large number of recommendations (over 400,000) since 1985.…”
Section: The Samplementioning
confidence: 99%
“…The Wall Street Journal evaluated the effectiveness of analysts" recommendations, comparing the results with those of a group of stocks selected at random (dartboard portfolio) and also with the Dow Jones. The outcome from this comparative study was that the analysts" perform slightly better, if one does not take into account dividends and investors" risk (Walker and Hatfield, 1996). Barber, Lehany McNichols and Trueman (2001), utilizing data from Zack"s data base, found an excess return of 4% for stocks which attracted a "strong buy" recommendation.…”
mentioning
confidence: 98%
See 1 more Smart Citation